Effectiveness of Work Training Program Overcoming Unemployment in Job Training Center Mojokerto - Nesy Hari Pratiwi; Agus Widiyarta (Universitas Medan Area, 2023)
This article aims to determine the effectiveness of the job training program at the Mojokerto Job Training Center (BLK). The problem focused on the effectiveness of the job training program at BLK Mojokerto in tackling unemployment. To approach this problem, a theoretical reference from Budiani (2007) on the theory of program effectiveness is used which measures effectiveness using four indicators, namely program accuracy, program socialization, program objectives and program monitoring. The data were collected through qualitative descriptive research methods, where the data collection techniques used observation, interview and documentation techniques. The data sources used are primary and secondary data and analyzed qualitatively. This study concluded that based on the results of research conducted by the author on the effectiveness of the job training program at BLK Mojokerto analyzed based on four indicators, including: accuracy of program targets, program socialization, program objectives and program monitoring showed that BLK Mojokerto had met these four indicators, so that the training program held could be said to be effective and could help participants to improve skills and the expertise he has.